2008
DOI: 10.1080/01421590802047257
|View full text |Cite
|
Sign up to set email alerts
|

A simulation-based biodefense and disaster preparedness curriculum for internal medicine residents

Abstract: A simulation-based biodefense and disaster preparedness curriculum for internal medicine residents, Medical Teacher, 30:6, e145-e151, DOI: 10.1080/01421590802047257To link to this article: https://doi.org/10.1080/01421590802047257 AbstractAims: Disaster and bioterrorism preparedness is poorly integrated into the curricula of internal medicine residency programs. Given that victims may present to a variety of healthcare venues, including primary care practices, inpatient hospital wards, and intensive care unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…32 Summerhill utilized a prospective cohort design to help show how human simulation increased internal medicine resident’s scores on bioterrorism written tests. 70 Miller showed that health professionals (mostly EMS) would improve their confidence after using human simulators in a HAZMAT scenario. 12 Vincent had medical students listen to podcasts about triage and then showed that students would improve triage accuracy after repeating scenarios with human patient simulators.…”
Section: Discussionmentioning
confidence: 99%
“…32 Summerhill utilized a prospective cohort design to help show how human simulation increased internal medicine resident’s scores on bioterrorism written tests. 70 Miller showed that health professionals (mostly EMS) would improve their confidence after using human simulators in a HAZMAT scenario. 12 Vincent had medical students listen to podcasts about triage and then showed that students would improve triage accuracy after repeating scenarios with human patient simulators.…”
Section: Discussionmentioning
confidence: 99%
“…One study indicated that a successful drill improved participants’ knowledge base, but that the enhanced effect had diminished a year later (12). Another report found that 1 year after the 2013 Boston bombings, experience at that event still remained a valuable platform for effective preparedness (13).…”
Section: Phase 3: Opportunities For Concentration and Competencementioning
confidence: 99%
“…9 Because of the lack of appropriate training in undergraduate medical courses, it is unlikely that general physicians can address disastrous health events as expected. 10 Pfenninger et al, after a review of existing studies, indicated there were very few reported curricula and courses on health management in crises for medical students. 11 In order to enhance the knowledge and skills of medical students on how to understand the health-related issues in crises and to promote their ability to manage and deal with crises, such courses and curriculums for medical education are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…11 In order to enhance the knowledge and skills of medical students on how to understand the health-related issues in crises and to promote their ability to manage and deal with crises, such courses and curriculums for medical education are necessary. 10 This study was conducted at the Kurdistan University of Medical Sciences in Iran. The aim of the study was to design and develop a course on "health management in crisis" for medical students in order to enable them to cope with and the address health-related issues in crises at graduation and beyond.…”
Section: Introductionmentioning
confidence: 99%